MiR‐124 and miR‐9 mediated downregulation of HDAC5 promotes neurite development through activating MEF2C‐GPM6A pathway. Issue 1 (19th May 2017) - Gu, Xi; Fu, Congcong; Lin, Lifang; Liu, Shuhu; Su, Xiaohong; Li, Aili; Wu, Qiaoqi; Jia, Chunhong; Zhang, Peidong; Chen, Lu; Zhu, Xinhong; Wang, Xuemin
Abstract : The class IIa histone deacetylases (HDACs) play important roles in the central nervous system during diverse biological processes such as synaptic plasticity, axon regeneration, cell apoptosis, and neural differentiation. Although it is known that HDAC5 regulates neuronal differentiation, neither the physiological function nor the regulation of HDAC5 in neuronal differentiation is clear. Here, we identify HDAC5 as an inhibitor of neurite elongation and show that HDAC5 is regulated by the brain enriched microRNA miR‐124 and miR‐9. We discover that HDAC5 inhibits neurite extension both in differentiated P19 cells and primary neurons. We also show that the neuronal membrane glycoprotein GPM6A (M6a) is a direct target gene of HDAC5 regulated transcriptional factor MEF2C. HDAC5 inhibits neurite elongation, acting at least partially via a MEF2C/M6a signaling pathway. We also confirmed the miR‐124/miR‐9 regulated HDAC5‐MEF2C‐M6a pathway regulates neurite development in primary neurons. Thus, HDAC5 emerges as a cellular conductor of MEF2C and M6a activity and is regulated by miR‐124 and miR‐9 to control neurite development. Abstract : We provide evidence that through the direct repression of HDAC5, miR‐124, and miR‐9 intrinsically regulate MEF2C transcription activity and M6a expression, and this ensures proper neurite elongation. Our findings further suggest that by acting in neurons, brain‐enriched miRNAs can play key roles in coordinating vertebrate central nervous system development.